Intraday Analysis of the Malaysian Stock Index Futures Market - Lim, Chee Seong (2004)
The use of any aggregate financial data to examine the relationship between information and prices using daily, weekly and monthly data leads to loss of information. The problem with such studies that employ time aggregated data is that it ignores the real time price dynamics and intraday interaction of the markets. Generally, most Malaysian financial economists have employed such inadequate methods. Specifically, for the Malaysian futures market, the intraday properties of the Kuala Lumpur Stock Exchange Composite Index (KLCI) futures contracts (FKLI) have not thoroughly examined, and hence, not well understood. Intraday analyses are crucial for investors and policy makers since many of the price adjustments could have taken place during the trading hours. Such real time adjustments can only be captured effectively by the intraday price analysis. In this study, the intraday data of 5-minute and 15-minute intervals of KLCI and FKLI is used to investigate the intraday price discovery mechanism, trading activity, volatility characteristics and spillover effects which has not been examined before by proir studies. The causal effect of both markets is measured by the computation of the bivariate Granger causality. The intraday lead and lag relationships between the KLCI and FKLI were examined under the orientation of multiple regression analysis. The short run dynamics of the volatility movement of the two markets is studied by the impulse response functions. In addition, in order to study the intraday volatility spillover between the cash and futures markets, the Bivariate Error Correction- Exponential Generalised Autoregressive Conditional Heteroscedasticity (ECMEGARCH) model is employed to capture the long-run equilibrium relationship, shortrun causality effect and the nature of the time varying variance in the series. Besides, this model is also used to investigate the asymmetric impact of shocks on stock and futures markets volatility, known as the leverage effect. The empirical evidence obtained from this study indicates that the intraday price volatility of FKLI does not exhibit a convex U-shaped pattern but instead a ‘reverse Jshaped’ pattern. However, the conventional U-shaped curve exists in the tick volume analyses. The results from the bivariate cointegration analysis are in line with those found in the developed markets. The futures prices appear to react more rapidly to new information as compared to the cash prices. The study of lead and lag relationships between the futures and cash markets revealed a bi-directional relationship. The futures returns tends to lead strongly the cash returns, in the time period up to 20 minutes; while the cash returns leads weakly the futures returns, in the time period between 5 to 10 minutes. Generally, the futures index consistently indicates a stronger degree of price discovery and price leadership over the cash index.The bivariate EGARCH analysis of volatility spillover found that there is a persistent bi-directional information flow between the futures and cash markets. It implies that innovations in the futures market could predict the future volatility of the cash market, or vice versa. However, the futures index has a higher degree of volatility spillover as compared with the cash index. Thus, it can be used by market participants to anticipate the future performance of the cash index. Finally, both markets exhibit the asymmetric volatility effects as predicted. In other words, any bad news tends to create greater impact on volatility, than the good news, for both markets. In conclusion, the interesting microstructure discoveries with a reverse J-shape for volatility and a U-shape for tick volume is definitely important for all market participants. As a result, investors with different risk appetite should be able to time their trades in accordance with the volatility and trading activity patterns of FKLI revealed in this study. In terms of price leadership and price discovery, the futures index seems to play a more dominant role in the information transmission mechanism of the two markets, as it possesses a stronger degree of price leadership over the cash index. Hence, the futures index can be perceived as a vehicle for price discovery and the performance of the intraday futures prices can be used by traders to predict the future movements of the cash prices. Finally, emphasizing that volatility is a proxy for information flow, the bivariate ECM-EGARCH analysis indicates that a bi-directional volatility spillover exits between the KLCI and the FKLI markets. However, the spillovers from the futures market to the cash market are more significant and prominent than the reverse. These results are consistent with the evidence supporting the dominant role of FKLI in price discovery. Therefore, it is proven that the futures market is more informationally efficient than the cash market.